Effect of Housing Layout and Open Space Morphology on Residential Environments–Applying New Density Indices for Evaluation of Residential Areas Case Study: Tehran, Iran - Sepideh Payami Azad; Ryohei Morinaga; Hideki Kobayashi (Journal of Asian Architecture and Building Engineering, 2018)
Over time, urban developments with increased densities have led to a decrease in private open space with a lack of public open space. Residential open spaces are missing in housing legislations as they are estimated based on floor area ratio and building coverage ratio, whereas they cannot be used as an all-encompassing measurement tool. Moreover, it is important for designers to consider housing layout to ensure a pleasant environment for residents; eventually, a range of benefits and opportunities will be available in residential open spaces. Therefore, to achieve a better quality of space in residential areas, new indices in the evaluation of residential environments should be proposed. This research assumes that there are links between the attributes of housing layout, space openness, and quality of space in residential areas. This study intends to examine some of the effects of housing layouts on residential open space through a comparative analysis of residential areas in Tehran. The relation between building arrangements, possibility of windows, and spatial openness will be analyzed; subsequently, two new indices—wall perimeter index (WPI) and spatial openness index (SOI)—will be proposed and target districts will be studied to compare different residential areas according to the new indices.